1992
DOI: 10.1038/bjc.1992.272
|View full text |Cite
|
Sign up to set email alerts
|

Suramin prevents neovascularisation and tumour growth through blocking of basic fibroblast growth factor activity

Abstract: Summary Inhibition of angiogenesis through blocking of growth factors involved in this process could be a novel therapeutic approach in several important pathologies, neoplasia among them. Suramin has recently been described to possess antineoplastic activity in animals and humans, and it has been proposed that an important role in this activity is played by antagonism of growth factors and especially bFGF. To investigate this hypothesis in vivo, we used gelatin sponges loaded with bFGF and implanted subcutane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
54
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(57 citation statements)
references
References 24 publications
3
54
0
Order By: Relevance
“…The study of Pesenti et al (1992) has shown that i.v. suramin is able to block bFGF-induced vascularisation of a gelatin sponge implanted subcutaneously in rats.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study of Pesenti et al (1992) has shown that i.v. suramin is able to block bFGF-induced vascularisation of a gelatin sponge implanted subcutaneously in rats.…”
Section: Methodsmentioning
confidence: 99%
“…We have employed a similar model to examine the antiangiogenic activity of the related polyanions. A polyether sponge was employed rather than the gelatin sponge of Pesenti et al (1992), which unlike the gelatin sponge spontaneously vascularises slowly as a result of an inflammatory response.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The antiangiogenic activity of suramins is based, at least in part, on their ability to disrupt the interaction of many growth factors with their membrane receptors, such as in the case of FGFs and their tyrosine kinase receptors (19, 24 -26). Because it has been shown that heparin disrupts aFGF⅐suramin complexes (27) and counteracts the antiangiogenic effect of these polysulfonated ureas (25,26), suramins are considered to act by blocking the heparin-binding sites of FGFs (28). Another group of antiangiogenic and antitumoral compounds is comprised by suradistas, a type of noncytotoxic synthetic binaphthalene sulfonic distamycin-A derivatives.…”
mentioning
confidence: 99%
“…This assay, initially developed by Folkman (1975) to study tumour-induced angiogenesis, is now widely used as an resulted in inhibition of angiogenesis on all the eggs tested, but this concentration of LAM S5 was associated with increased toxicity to the chick embryos (Table I). Suramin, which has anti-angiogenic activity (Pesenti et al, 1992) and was used as a positive control in our studies, had less antiangiogenic activity than LAM S5 (Table I). Several polysulphated carbohydrates with anti-angiogenic activity have also been shown to inhibit tumour growth in animal models (see introduction).…”
Section: Resultsmentioning
confidence: 95%